A NEW METHOD FOR THE DETERMINATION OF CEIII/CEIV RATIOS IN GEOLOGICAL MATERIALS; APPLICATION FOR WEATHERING, SEDIMENTARY AND DIAGENETIC PROCESSES - Takahashi Y.; Shimizu H.; Kagi H.; Yoshida H.; Usui A.; Nomura M. (My University, 2000)
Relative abundances of rare earth elements (REE) in geological materials are used widely to investigate diverse geochemical issues such as the origins of igneous rocks or the degree of stratification of water columns in oceans. One of the REE, cerium (Ce), can exist in either trivalent or tetravalent forms depending on the redox condition. Thus, knowledge of the oxidation state of Ce in rocks and minerals could potentially be used to constrain the redox states of past and present geological environments. However, the use of Ce for this purpose has been hampered by an inability to measure its oxidation state directly. Here, we present a new method, employing the X-ray absorption near-edge structure, for making such determinations in samples with Ce concentrations as low as 15 ppm. By analyzing a range of diverse geological materials (granites, manganese nodules and cherts), we showed that the method could identify significant differences in Ce speciation between materials formed under widely differing redox conditions. Used together with the degrees of Ce anomalies measured in REE patterns, this information has promise for refining our knowledge of various geochemical processes such as weathering, sedimentary and diagenetic processes that control the REE behavior. Such a refinement should in turn improve geological interpretations based upon REE data.
Keywords: CERIUM; ISOTOPE RATIOS; X-RAY ANALYSIS; GEOCHEMICAL ANOMALIES; GRANITES; NODULES; CHERT